Morphometric Examination Of Mastoid Air Cells By Using Ct Method - Kavaklı, Ahmet; Karakaş, Sacide; Uzun, Ahmet (Fırat University, 2002)
Aim: A lot of variations may be noticed in shape and size in mastoid air cells. CT in diagnosis, although many studies were done, by using in these studies age groups were not usually established and the volumes of mastoid air cells were not compared in detail. Therefore in this study, it was planned the classification of mastoid pneumatization, the relationship between right and left sides and the comparison of development progresses according to the age and sex with the results of the CT scans. Material and Method: Of all patients applied to radiology department, 91 cases without any mastoid air cells pathology (like inflammation, operation or trauma) were selected for evaluation. Axial CT scans obtained from temporal bones of all cases. In all scans, the volumes of each area mastoid air cell were calculated and analysed statistically. Results and Conclusion: At the results, it was noticed that the volumes of mastoid air cells increased with the age and women had lower mean volume. When we correlated right-left and ipsilateral structures mastoid air cells, it was determined that there was a positive correlation between them. The mean volumes were near to the results on the literature. The percentage of pneumatic mastoid was 97.80 %, apneumatic mastoid was 2.19 %.

Amaç: Cellulae mastoideae şekil ve büyüklük açısından birçok farklılıklar gösterebilir. Bilgisayarlı Tomografi'nin (BT) tanıda kullanılmasından sonra bu konuda çalışmalar yapılmış olmasına karşın, yapılan çalışmalarda genellikle yaş grupları oluşturulmamış ve cellulae mastoideae hacimleri (CMH) geniş şekilde araştırılmamıştır. Bu nedenle BT kullanarak elde ettiğimiz verilerden yaş ve cinsiyete göre gelişme seyirlerini, sağ-sol taraf arasındaki ilişkileri ve mastoid havalanma ile ilgili oranları tespit etmeyi bu çalışmamızda amaçladık. Gereç ve Yöntem: BT tetkiki için Radyoloji Anabilim Dalına başvuran, herhangi bir patolojisi (geçirilmiş enfeksiyon, ameliyat veya travma) olmayan toplam 91 olgu (47 erkek, 44 kadın) seçildi. Her olguya os temporale aksiyel BT tetkiki yapıldı. Elde edilen her kesitte CMH ayrı ayrı hesaplandı ve istatistiksel analizleri yapıldı. Bulgular ve Sonuç: Yapılan analizler sonucunda CMH yaşla birlikte düzenli olarak arttığı, bunun yanında kadınların erkeklerden daha düşük hacim ortalamalarına sahip olduğu görüldü. Elde edilen hacim ortalamaları kaynaklarla karşılaştırıldığında verilerin birbirlerine yakın oldukları görüldü. Olgular incelendiğinde pnömatize mastoidin %97.80 ve apnömatik mastoidin %2.19 oranında olduğu tespit edildi.
MASTOİD HAVA HÜCRELERİNİN BİLGİSAYARLI TOMOGRAFİ YÖNTEMİYLE MORFOMETRİK İNCELENMESİ